La yuca: una fuente básica de energía en los trópicos - Cock, James H. (International Center for Tropical Agriculture, 1984)
Cassava is the 4th most important source of food energy in the tropics. More than 2/3 of the total production of this crop is used as food for humans, with lesser amounts being used for animal feed and industrial purposes. The ingestion of high levels of cassava has been associated with chronic cyanide toxicity in parts of Africa, but this appears to be related to inadequate processing of the root and poor overall nutrition. Although cassava is not a complete food it is important as a cheap source of calories. The crop has a high yield potential under good conditions, and compared with other crops it excels under suboptimal conditions, thus offering the possibility of using marginal land to increase total agricultural production. Breeding programs that bring together germplasm from different regions coupled with improved agronomic practices can markedly increase yields. The future demand for fresh cassava may depend on improved storage methods. The markets for cassava as a substitute for cereal flours in bakery products and as an energy source in animal feed rations are likely to expand. The use of cassava as a source of ethanol for fuel depends on findingan efficient source of energy for distillation or an improved method of separating ethanol from water. (AS)